2022
DOI: 10.1002/jbm.b.35172
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized fish swim bladder patch loaded with mesenchymal stem cells inhibits neointimal hyperplasia

Abstract: We previously showed decellularized fish swim bladder can be used as vascular patch and tube graft in rats, mesenchymal stem cells (MSCs) have showed the capability to inhibit neointimal hyperplasia in different animal models. We hypothesized that decellularized fish swim bladder patch loaded with MSCs (bioinspired patch) can inhibit neointimal hyperplasia in a rat aortic patch angioplasty model. Rat MSCs were grown in vitro and flow cytometry was used to confirm their quality. 3.6 Â 10 5 MSCs were mixed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Li et al [ 2 ] confirmed that AFSB utilized as a dura mater substitute can meet the demands of clinical applications. Liu et al [ 3 ] prepared AFSB-based scaffolds crosslinked by glutaraldehyde (GA) for cardiovascular diseases, which showed superior anti-calcification properties and biocompatibility compared to bovine pericardium, revealing their promising application for use in cardiovascular biomaterials [ 4 , 5 , 6 ]. Furthermore, AFSBs have also shown potential for use in several fields, such as wound healing [ 7 ], cervical oesophagoplasty [ 8 ] and cystoplasty [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 2 ] confirmed that AFSB utilized as a dura mater substitute can meet the demands of clinical applications. Liu et al [ 3 ] prepared AFSB-based scaffolds crosslinked by glutaraldehyde (GA) for cardiovascular diseases, which showed superior anti-calcification properties and biocompatibility compared to bovine pericardium, revealing their promising application for use in cardiovascular biomaterials [ 4 , 5 , 6 ]. Furthermore, AFSBs have also shown potential for use in several fields, such as wound healing [ 7 ], cervical oesophagoplasty [ 8 ] and cystoplasty [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fish swim bladders (FSBs) used to be considered as garbage in fishery (Yadav et al 2019 ), however, with the well-aligned natural collagen nano-fibrils, they have been applied in biomedical fields at present, such as the bio-piezoelectric nanogenerator used as a sensor (Ghosh and Mandal 2016 ). Meanwhile, after decellularization treatment, acellular fish swim bladders (AFSBs) with high content of collagen, excellent biocompatibility and biodegradable properties (Shahabipour et al 2013 ; Yazdani Moghaddam et al 2009 ), have been used as tissue engineering scaffolds in several fields (Bai et al 2021 ; Li et al 2021a , b ; Sun et al 2022 ). The outstanding advantage of scaffolds with AFSBs is that they can decrease the risk of foot and mouth disease, bovine spongiform encephalopathy and immune response when compared with mammalian-derived materials (Kim and Mendis 2006 ).…”
Section: Introductionmentioning
confidence: 99%